Consensus based good practice guidelines for clinical psychologists working in and with homelessness: a Delphi study - Wells, Jennifer (2021)
The number of those considered homeless – including the hidden homeless - has been increasing since 2010 (Fransham, 2018). Legislation, such as the Homelessness Reduction Act (2017), has been introduced to tackle rising numbers. This is the first piece of legislation to acknowledge the complexity and prevalence of mental health difficulties in the homeless population, repeatedly highlighted in the literature. Despite increasing numbers, complexity, links to mental health difficulties and backgrounds characterised by trauma, Clinical Psychologists (CPs) currently have no guidelines to support their direct work with this population, nor the organisations and staff they work with. Furthermore, this lack of guidance means commissioners have no way of knowing the resources required for CPs to work effectively with this population. Despite the absence of an empirical evidence base, CPs have been working in homelessness services, meaning they will have generated practice-based evidence. This research sought to harness this practice-based evidence and create consensus-based good practice guidelines.